Understanding the teaching of english as a foreign language at rural school Agua Clara (2017)
The school Agua Clara is part of the educational institutions that belong to the so-called multigrade classrooms. In this institution, the students are oriented by only one teacher, who do many functions in the school. In addition to guide the teaching and learning process of all areas. According to the needs of today's society, children must learn English from the beginning of their school years. Therefore, the teacher of the school Agua Clara, has the function of guiding the English’s teaching and learning process, at all grades from preschool to fifth grade. In the following work, I will be announced the experiences that the teacher of the school Agua Clara has had during the process of teaching and learning English as a foreign language, this is my motivation as researcher, to show how the teaching of English occurs in this school with this teacher who has 21 students, from different ages and levels. Agua Clara is a rural school, where occurs many things at the same time, there is observed a passive learning and students are great little people who wants to learn a lot of English, and at the same time they are very responsible with the implications of the work in farm. I selected this school, so I wanted to show the teaching process and all aspects that are involved in it. For example, there is a classroom with different levels, a teacher that has to face the teaching in a good environment, in a passive place, with few materials to work, but she uses children and the space to make a great teaching.